2014
DOI: 10.1002/jts.21939
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Perinatal Stress and Maternal Traumatic Stress on the Cortisol Regulation of Preterm Infants

Abstract: Preterm infants experience intense stress during the perinatal period because they endure painful and intense medical procedures. Repeated activation of the hypothalamic-pituitary-adrenal (HPA) axis during this period may have long-term effects on subsequent cortisol regulation. A premature delivery may also be intensely stressful for the parents, and they may develop symptoms of posttraumatic stress disorder (PTSD). Usable saliva samples were collected (4 times per day over 2 days, in the morning at awakening… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 14 publications
0
7
0
1
Order By: Relevance
“…Cortisol, the primary stress hormone, also helps a fetus to develop and is responsible for triggering the birth process. Cortisol could also contribute to premature labor [96,97,98,99]. Long-term activation of the stress-response system, high-intensity of stressful conditions, and the subsequent overexposure to cortisol and other stress hormones can lead to adverse pregnancy outcomes [100,101].…”
Section: Discussionmentioning
confidence: 99%
“…Cortisol, the primary stress hormone, also helps a fetus to develop and is responsible for triggering the birth process. Cortisol could also contribute to premature labor [96,97,98,99]. Long-term activation of the stress-response system, high-intensity of stressful conditions, and the subsequent overexposure to cortisol and other stress hormones can lead to adverse pregnancy outcomes [100,101].…”
Section: Discussionmentioning
confidence: 99%
“…In our sample, only full-term children were traumatized by family issues, such as parental separation. The literature also highlights an increased risk of post-traumatic disorders in mothers of prematurely born children (Holditch-Davis et al, 2003; Kersting et al, 2004; Muller-Nix et al, 2004), and in the prematurely born neonates themselves, cortisol, a stress indicator, higher than the average has been underlined (Habersaat et al, 2014a, 2014b). More investigation regarding the maternal disorder and the trauma it can incur on the children is needed.…”
Section: Discussionmentioning
confidence: 99%
“…Medical risk and the long postnatal hospitalizations, rather than prematurity itself, may influence both infant self-regulation and parental stress (Bonifacio et al, 2010; Miceli et al, 2000). It is well known that these factors can affect the neurocognitive development (Bonifacio et al, 2010; Miceli et al, 2000) and the quality of the early dyadic interaction, which in turn affects children’s psychological development (Fuertes et al, 2006; Habersaat et al, 2014a; Muller-Nix et al, 2004; Pierrehumbert et al, 2003; Stramrood et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Capik (1) found that 11.9% of healthy spontaneous pregnancies are stressful due to pregnancy. Other studies have shown that pregnancy with assisted reproductive therapy (ART) (2)(3)(4)(5)(6) , gestational diabetes mellitus (GDM) (7)(8)(9) , preterm labor diagnosis (PLD) (10,11) and hypertensive disorders (12) cause stress for pregnant women. In addition, systemic (such as anemia and hypertension) and pregnancy-related disorders (such as Rh incompatibility, placental abnormalities, intrauterine growth retardation, hyperemesis gravidarum (HEG), infection, oligohydramnios, and cholestasis) can increase stress (13,14) .…”
Section: Introductionmentioning
confidence: 99%